On the nature of the phase transition in SU(N), Sp(2) and E(7) Yang-Mills theory - Braun, Jens; Eichhorn, Astrid; Pawlowski, Jan M. (The European physical journal. C, Particles and fields, 2010)
We study the nature of the confinement phase transition in d=3+1 dimensions in various non-abelian gauge theories with the approach put forward in Phys. Lett. B 684, 262 (2010). We compute an order-parameter potential associated with the Polyakov loop from the knowledge of full 2-point correlation functions. For SU(N) with N=3,…,12 and Sp(2) we find a first-order phase transition in agreement with general expectations. Moreover our study suggests that the phase transition in E(7) Yang-Mills theory also is of first order. We find that it is weaker than for SU(N). We show that this can be understood in terms of the eigenvalue distribution of the order parameter potential close to the phase transition.